2012
DOI: 10.1186/cc11341
|View full text |Cite
|
Sign up to set email alerts
|

Early course of microcirculatory perfusion in eye and digestive tract during hypodynamic sepsis

Abstract: IntroductionThe aim of the study was to evaluate and compare the microcirculatory perfusion during experimental sepsis in different potentially available parts of the body, such as sublingual mucosa, conjunctiva of the eye, and mucosa of jejunum and rectum.MethodsPigs were randomly assigned to sepsis (n = 9) and sham (n = 4) groups. The sepsis group received a fixed dose of live Escherichia coli infusion over a 1-hour period (1.8 × 109/kg colony-forming units). Animals were observed 5 hours after the start of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 20 publications
(24 reference statements)
2
25
0
Order By: Relevance
“…These observations are in accordance with the results of previous porcine experiments using E. coli [1922]. Similar to our observations, Pranskunas and co-workers reported on a 2-fold increase of the systemic vascular resistance 5 h after injection of E.coli, accompanied by a gradual decrease of the cardiac index [20]. In a recent review models using continuous infusion of living bacteria are described as hypodynamic sepsis models [23].…”
Section: Discussionsupporting
confidence: 92%
“…These observations are in accordance with the results of previous porcine experiments using E. coli [1922]. Similar to our observations, Pranskunas and co-workers reported on a 2-fold increase of the systemic vascular resistance 5 h after injection of E.coli, accompanied by a gradual decrease of the cardiac index [20]. In a recent review models using continuous infusion of living bacteria are described as hypodynamic sepsis models [23].…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, we used the tongue as a window to observe the microcirculation. It is conceivable that other organs may express different microvascular abnormalities at baseline [18, 29], or in response to fluid administration [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Early alteration of microcirculatory blood flow was associated with poor outcome [6,7]. A time-dependent significant decrease in perfused vessels and microvascular flow index during a hypodynamic state of sepsis could be demonstrated in a pig model [8]. Moreover, it has been shown that microcirculatory dysfunction correlates with markers of endothelial activation in children suffering from meningococcal disease [9].…”
Section: Introductionmentioning
confidence: 97%